THE EFFECT OF USING VOCABULARY SELF-COLLECTION STRATEGY (VSS) ON STUDENT’S VOCABULARY MASTERY - Hutauruk, Desi Ramadali (Universitas Mahaputra Muhammad Yamin, 2023)
Vocabulary is one of the important elements in learning English that make students easy to master English skills; speaking, reading, listening and writing. However, many students lack of vocabulary mastery, so it was difficult for them to determine the meaning or words in context. Therefore, this research was intended to find out the significant effect of using vocabulary self-collection Strategy on student vocabulary mastery. This research used quantitative approach and design was pre-experimental with one group pre-test and post-test. The researcher used a total sampling technique because it only had one class with a total of 23 students in eighth grade at SMPN 2 Sorkam. Data was collected through a vocabulary test with a pre-test and post-test design of 30 questions. Based on the data analysis, the result exposed that t-obtain was 17.52 while the t-table was 1.717. It means that the hypothesis (Ha) was accepted while the null hypothesis (Ho) was rejected. Therefore, the finding of the data present that there is a significant effect of using self-collection strategy on student vocabulary mastery at eighth grade of SMPN 2 Sorkam.